2021
DOI: 10.1159/000518970
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Skin Penetration, Radical Protection, and Structural Changes after Topical Application of a Herbal Oil Cream Compared to Topical Calcipotriol in Mild to Moderate Psoriasis

Abstract: Background: The chronicity of psoriasis often requires continuous topical treatment. Materials and Methods: Here, the radical protection of a cream containing various herbal oils was evaluated in vivo by electron paramagnetic resonance (EPR) spectroscopy and its skin penetration by Raman microscopy in intact and barrier-disturbed skin. Changes in skin barrier properties were evaluated after 4 weeks of daily topical application using in vivo laser scanning microscopy (LSM) and transepidermal water loss in 26 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…The recent work [189] utilised EPR measurements to quantify the radical formation in vivo during the skin treatment by herbal oils as a time function, while the Raman spectroscopy gave information on the penetration depth using specific herbal compounds' spectral fingerprints. Therefore, this combined spatiotemporal information may play a role in the background for the future building of a kind of reaction-diffusion model of the process.…”
Section: Combining Epr and Raman Spectroscopy Methods And Datamentioning
confidence: 99%
“…The recent work [189] utilised EPR measurements to quantify the radical formation in vivo during the skin treatment by herbal oils as a time function, while the Raman spectroscopy gave information on the penetration depth using specific herbal compounds' spectral fingerprints. Therefore, this combined spatiotemporal information may play a role in the background for the future building of a kind of reaction-diffusion model of the process.…”
Section: Combining Epr and Raman Spectroscopy Methods And Datamentioning
confidence: 99%
“…[26][27][28] Several methods have been used to examine the psoriatic SC, like TEWL, corneometry, 'attenuated total reflectance-Fouriertransform infrared spectroscopy', 29,30 tape-stripping, 31 multiphoton CARS tomography, 32 optical coherence tomography, 33 diffuse reflectance spectroscopy, 34 scanning electron microscopy 35 and laser scanning microscopy. 36,37 Previous studies have revealed a less ordered SC structure regarding lipid organisation in psoriatic lesions, 10,36,38 which is thought to be partly due to differences in the composition of ceramides. 38,39 The FFA concentration of lesional psoriatic skin (LPS) has been found to be lower than of non-lesional psoriatic skin (nLPS).…”
Section: Introductionmentioning
confidence: 99%